BATAS TANGGUNG JAWAB PERUSAHAAN DALAM CORPORATE SOCIAL RESPONBILITY (CSR) - Anis Nur Nadiroh (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2020)
This research will be more directed to respond to the conception and understanding by default in implementing the conceptions and main components in CSR in Indonesia. CSR has covered seven main components, the seven components are the environment, social development, human rights, organizational governance, labor practices, fair operating practices, and consumer issues. The big idea that is being carried is about efforts to create an ideal and just law in accordance with the valuesand ideals of the country. CSR is not a form of transfer of the responsibility of the state towards its people. The method used in this research is juridical normative. The results of this study convey that so far there has not been a standard understanding in interpreting CSR itself, both in terms of the Limited Liability Company Law and the Investment Law. As a result of these differences, the boundaries of corporate responsibility in carrying out its social responsibilities to the community lack clarity and certainty, likewise the companies also lack maximum effort to carry out social responsibility to the community